1983
DOI: 10.1051/rnd:19830501
|View full text |Cite
|
Sign up to set email alerts
|

Déterminisme neuro humoral de l'adaptation de l'intestin résiduel après entérectomie

Abstract: Summary. Neurohumoral

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1985
1985
2008
2008

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 134 publications
1
0
0
Order By: Relevance
“…This was confirmed as it was shown that compensatory mucosal hypertrophy after small bowel resection was severely impaired by vagal deafferentation [101,102]. This suggested that, besides intrinsic control factors of epithelial renewal, the visceral sensitivity supported by vagal afferences might be a determinant of true adaptation as a result of the homeostatic control of functional digestive ability.…”
Section: Central and Peripheral Control Of Food Intake And Digestive supporting
confidence: 60%
“…This was confirmed as it was shown that compensatory mucosal hypertrophy after small bowel resection was severely impaired by vagal deafferentation [101,102]. This suggested that, besides intrinsic control factors of epithelial renewal, the visceral sensitivity supported by vagal afferences might be a determinant of true adaptation as a result of the homeostatic control of functional digestive ability.…”
Section: Central and Peripheral Control Of Food Intake And Digestive supporting
confidence: 60%